PENGARUH KONSENTRASI EKSTRAK BAWANG MERAH DAN AIR KELAPA TERHADAP PERTUMBUHAN STEK TANAMAN MELATI PUTIH (Jasminum sambac L.) - Hadriman Khair; Meizal ,; Zailani Rizky Hamdani (AGRIUM: Jurnal Ilmu Pertanian, 2013)
This study aims to determine the effect of shallots extract and coconut water as well as the interaction between shallots extract and coconut water on the growth jasmine plant by using  randomized design group with two factors studied namely : coconut water (A) which consist of four standard that A0 = without giving, A1 = concentration 20% (200 cc/l), A2 = concentration 25 % (250 cc/l), A3 = concentration 30 % (300 cc/l) while shallots extract (B) which consist of four standard that B0 = without giving, A1 = concentration 0,5 % (5 cc/l), A2 = concentration 1 % (10 cc/l), A3 = concentration 1,5 % (15 cc/l). coconut water as the first factor and shallots extract as a second factor.Key words : growth, jasmine, coconut water, shallots extract